Antiviral and Immunomodulatory Properties of Antimicrobial Peptides Produced by Human Keratinocytes - Chessa, Céline; Bodet, Charles; Jousselin, Clément; Wehbe, Michel; Lévêque, Nicolas; Garcia, Magali (Frontiers in Microbiology, 2020)
Keratinocytes, the main cells of the epidermis, are the first site of replication as well as the first line of defense against many viruses such as arboviruses, enteroviruses, herpes viruses, human papillomaviruses, or vaccinia virus. During viral replication, these cells can sense virus associated molecular patterns leading to the initiation of an innate immune response composed of pro-inflammatory cytokines, chemokines, and antimicrobial peptides. Human keratinocytes produce and secrete at least nine antimicrobial peptides: human cathelicidin LL-37, types 1–4 human β-defensins, S100 peptides such as psoriasin (S100A7), calprotectin (S100A8/9) and koebnerisin (S100A15), and RNase 7. These peptides can exert direct antiviral effects on the viral particle or its replication cycle, and indirect antiviral activity, by modulating the host immune response. The purpose of this review is to summarize current knowledge of antiviral and immunomodulatory properties of human keratinocyte antimicrobial peptides.